2021
DOI: 10.1038/s41522-021-00190-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of oral virome and microbiome revealed distinctive microbiome disruptions in paediatric patients with hand, foot and mouth disease

Abstract: While the underlying determinants are unclear, hand, foot and mouth disease (HFMD) presents a wide spectrum of clinical manifestations with varying severity in different individuals. Recently, many studies identified the human microbiome as a critical factor in the pathogenesis of various diseases. Therefore, we here investigated the ecological dynamics of the oral microbiome changes during the HFMD infection. After targeted enrichment of all known vertebrate viruses, the virome profiles of symptomatic and asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Streptococcus , which is one of the most classic opportunistic pathogens, comprises a wide variety of pathogenic bacterial strains. Streptococcus is one of the most prevalent inhabitants of the respiratory tract ( Engholm et al., 2017 ), skin surface ( Ho et al., 2021 ) and gut ( Sokol et al., 2017 ; Ooi et al., 2018 ) of adults and children. Studies have shown that influenza virus can interact with S. pneumoniae and induce susceptibility to viruses by activating cytokines and dendritic cells ( Short et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus , which is one of the most classic opportunistic pathogens, comprises a wide variety of pathogenic bacterial strains. Streptococcus is one of the most prevalent inhabitants of the respiratory tract ( Engholm et al., 2017 ), skin surface ( Ho et al., 2021 ) and gut ( Sokol et al., 2017 ; Ooi et al., 2018 ) of adults and children. Studies have shown that influenza virus can interact with S. pneumoniae and induce susceptibility to viruses by activating cytokines and dendritic cells ( Short et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations on the ecological niche of the patients affected with hand foot and mouth disease showed nine discriminative viral species with elevated levels of Streptococcus sp.,. It also correlated with the presence of Enterovirus and Coxsackievirus A5 and A6 together with the altered virome profiles [30] . On the other hand, a healthy human microbiome may be always accustomed with the direct health of the human body.…”
Section: Oral Viromementioning
confidence: 84%
“…In a previous study, Ho et al investigated the ecological dynamics of the oral microbiome changes during the HFMD infection. All known vertebrate viruses in the specimens were under targeted enrichment before the detection of the viruses, and nine discriminative viruses were detected [ 34 ]. Although in Ho’s study, the specimens were from mouths, and in our study, the specimens were from feces, and the viral enrichment can improve the sensitivity of virus detection.…”
Section: Discussionmentioning
confidence: 99%